Using Instagram to Improve Students’ Ability and Interest in Writing Descriptive Paragraph - Saipul Renaldi (Journal La Edusci, 2020)
This research aimed at finding out the improvement of the students’ writing ability and interest by using Instagram as media. To find out the improvements, the writer used pre-experimental design with one group pre-test and post-test design and questionnaire. The population of this research was the eleventh-grade students’ at SMA Muhammadiyah 1 Unismuh Makassar, academic year 2017/2018. The sample was class XI IPA taken by purposive sampling technique which consisted of 10 students. It employed five meetings (one meeting for pre-test, three meetings for treatment, and one meeting for post-test and questionnaire). It employed writing test as instrument. The research findings indicated that the application of using Instagram was effective in improving the students’ writing skill in term of content and organization. It was proved by the value of the total t-test was 6.30, which was higher than the value of t-table (1.833). This indicated that (H1) was accepted, and (H0) was rejected. It means that there was a significant difference of the students’ writing skill before and after using Instagram in classroom. The students’ interest in writing also improved after the treatment. It was shown by students’ answers in the questionnaire. Most students gave positive respons toward the use of instagram to improve their interst in writing, even they think that this method can be applied in classroom to attract their attention and interest. Therefore, this research is very useful for learning process as a reference for teachers to teach in classroom.